L’evoluzione del rapporto di lavoro e della vita quotidiana delle donne dopo l’arrivo del primo figlio - Robin, Monique (Rivista Italiana di Educazione Familiare, 2011)
The aim of this qualitative study is to describe how the arrival of their first child changes the relationship of work and daily life of women. 59 working mothers with a young son have been met for an interview based on the path and work and family plans, on the rhythms of everyday family life. The results are based on a computerized text analysis which supports the semantic universe of the language used by women and the analysis of the contents of the interviews based on the management of everyday life and the projects in the professional field. The results show that if women had assigned to work an important meaning as part of their social identity, the arrival of a child leads to the construction of parental identity centered on the welfare of the child and the management of the quality of life in everyday family life.